Evaluation of Variability, Genetic Advancement and their Correlation in Triticum Aestivum L. - Naz, Amna; Abdur Rauf,; Bibi, Mamoona; Yaseen,; Iqra Ambreen,; Syeda, Khushnood; Aziz, Khayyam; Haseeba,; Zarghoona,; Afridi, Khilwat; Siddique, Aisha (Indus Journal of Bioscience Research, 2024)
The current research was conducted with the objective to estimate evaluation of variability, genetic advance and correlations in wheat. Sixty-four wheat advance lines were grown in alpha lattice designed during 2022-2023 at Cereal Crops Research Institute (CCRI), Pirsabak Nowshera, Pakistan. Significant differences among genotypes were recorded shown through analysis of variance. Days to heading ranged from 116 days to138 days, flag leaf area ranged from 18cm2-40cm2, plant height ranged from 84 cm -111 cm, tiller m-2 ranged from 136-424, grain yield from 3240 kg/ ha to 6051 kg/ ha and thousand grain weight ranged from 31g-52 g. Maximum value of GCV reported for tiller per spike (20.2), while minimum value recorded for days to heading (2.70), while high PCV value recorded for1000 grain weight was (25.02), while lowest value recorded for grain yield (0.27). Magnitude of heritability was higher for grain yield (2358) and it was recorded moderate for thousand grain weight (0.50). Maximum value of genetic gain recorded for tiller-2 (65.38) and it was minimum for days to heading (3.73). The findings indicated strong and positive link between grain yield with plant height (r=0.30**), days to heading have a negative correlation with qualities that contribute to production, such as grain yield and 1000-grain weight.